Targeting the hTRPV6 with capsaicinoid inhibitors - Cunha, Micael Rodrigues (2019)
Capsaicin is a substance produced by Capsicum peppers with extensive biological activity reported in the literature. Among these studies, it was suggested that the anti-tumor activity is related to modulation of the Transient Potential Receptor Vanilloid (TRPV) channels. Capsaicin is known to bind with very high affinity to TRPV1 (IC50 ≈ 7 nM), triggering the burning sensation followed by analgesia. However, recent studies have suggested that the pro-apoptotic effects of capsaicin are TRPV6-mediated. Herein we report the development of a novel inhibitor of the TRPV6 using two different strategies for compounds design. We generated a series of direct and chimeric capsaicinoids based on the literature compounds, capsaicin, and cis-22a. These analogs were probed against HEK-hTRPV6 and the hits were further optimized. Based on the previous SAR and chemical optimization, we found 56h, named MRC-130, a derivative that remarkably inhibited TRPV6 in the nanomolar range (IC50 = 83 ± 4 nM), possess high selectivity and stability in vitro, and lesser hERG inhibition compared to the reference compound, cis-22a. It is expected that these new molecules would contribute significantly to the study on the TRPV6 function and its role in tumor pathophysiology.